(untitled) (قضايا سياسية, 2022)
There is a tangible change in the performance of Chinese foreign policy after the Chinese decision-makers realized that the Cold War era has passed forever، and that the directions of strategic openness through what some call the form of consultations will be in its purest form to consolidate the consensus between the active international powers that seem to They are unanimously agreed to avoid major escalation conflicts، and to slow the spread of technologies that may threaten them as a clear and sober introduction to bypassing the framework of the narrow circle that controls the interactions of international relations today، Whoever thinks that the Chinese leadership، with all its hierarchy of self-direction، will deliberately، with all its might، and perhaps be completely inclined، to elicit stimulating conditions for distributing the burdens of strengthening the international system، especially when it knows with certainty that the innovators of these activities resolved to close their performance options in the Chinese arena only. The similarity in that with the United States and its global rise a century ago is more than it has with the development of what preceded it and the forces that follow it in our present and future time. Today، China is witnessing a continuous and amazing growth of a future global power distinguished with vast، diverse and unprecedented sources.